Role Of Dental Doctor And Assistant In Composite Restoration (Journal of Namibian Studies : History Politics Culture, 2022)
Composite restoration is a common dental procedure aimed at restoring the form, function, and aesthetics of damaged or decayed teeth. This paper provides an overview of the roles of dental doctors (dentists) and dental assistants in composite restoration procedures. Dentists play key roles in diagnosis, treatment planning, tooth preparation, composite material application, bonding, curing, bite adjustment, and final polishing. On the other hand, dental assistants provide chairside assistance, ensure patient comfort, prepare equipment, operate suction and isolation devices, assist in sterilization, and offer post-operative instructions. Together, dentists and dental assistants collaborate to perform composite restorations effectively, ensuring optimal patient outcomes.